The dynamics of sports results and physical abilities of a highly skilled septathlete over a four-year Olympic cycle - Milasius, K.; Skernevicius, J.; Opalnikova, A. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The aim of the study was to analyse the dynamics of sports results of the Lithuanian septathlonist A.S. in a four-year Olympic cycle and the dynamics of her physical and functional abilities over this period. The conclusion of the study: Conclusions. The Lithuanian septathlete A.S. ranks among the world`s top-class athletes; she performed excellently at the XXVIII Olympic Games in Athens. Over the recent four years her skills kept increasing, though in the 2003 World championship she failed to improve the results and to win the 5th-6th place planned for her. If in the earlier years the septathlon contests of A.S., according to scores were divided into three groups (Milašius et. al., 2003), in the 2004 Olympic competitions the septathlon contests could be divided into two groups: group 1 where 15.1-14.4% were won (hurdling, high jump, shot-pot, long jump) and group 2 where 14.0-13.3% of scores were gained (200m running, javelin throwing, 800m running). In the final period of the preparation for the Olympic Games under a short-lasting load the muscular power of A.S. reached a high level and allowed her to realize physical and functional abilities.